On inflection - Steinkrüger, Patrick O.; Krifka, Manfred; Wurzel, Wolfgang Ullrich (Trends in linguistics. Studies and monographs ;, 2009)
The volume is dedicated to the German linguist Wolfgang Ullrich "Gustav" Wurzel (1940-2001), who has influenced linguistic thought in his work on paradigm-based morphology. All contributors to the volume deal with Wurzel's work and thinking, who in his theoretical writings focused on the concepts of naturalness, markedness and complexity in human language. The authors discuss diachronic and typological aspects of morphology, i.e. the nature of paradigms, the rise and fall of inflectional morphology, and the development and systems of gender marking, also in regard to the interface with phonology and syntax.